GAMING ADDICTION AS CULTURAL DEVIANCE: A SOCIO-PHILOSOPHICAL INTERPRETATION - Vafaeva Dilafruz Artikovna (Modern American Journals, 2025)
The article examines gaming addiction as a form of cultural deviance emerging within the rapidly evolving digital society. Based on a socio-philosophical approach, the study highlights the transformation of values and social norms under the influence of virtual environments, where gaming acts as an alternative space for self-realization and identity construction. Gaming addiction is interpreted not only as a psychological disorder, but also as a phenomenon rooted in modern cultural dynamics, including the dominance of entertainment practices, virtual achievements, and individualistic orientations. The analysis reveals that gaming-related deviance leads to a disruption of traditional socialization, weakening of interpersonal communication, and a shift in motivational priorities among youth. The article emphasizes the importance of understanding gaming addiction as a multidimensional cultural issue that requires the integration of educational, ethical, and social strategies aimed at forming responsible and conscious digital behavior.
Keywords: Gaming addiction; cultural deviance; socio-philosophical analysis; digital culture; virtual identity; socialization; youth environment; value transformation; digital society.